A Privacy-Preserving Continuous Location Monitoring System for Location-Based Services - Doohee Song; Jongwon Sim; Kwangjin Park; Moonbae Song (International Journal of Distributed Sensor Networks)
To protect users’ private locations in location-based services, various location anonymization techniques have been proposed. The most commonly used technique is spatial cloaking, which organizes users’ exact locations into cloaked regions (CRs). This satisfies the K -anonymity requirement; that is, the querier is not distinguishable among K users within the CR. However, the practicality of cloaking techniques is limited due to the lack of privacy-preserving query processing capacity, for example, providing answers to the user's spatial queries based on knowledge of the user's cloaked location rather than the exact location. This paper proposes a cloaking system model called anonymity of motion vectors (AMV) that provides anonymity for spatial queries. The proposed AMV minimizes the CR of a mobile user using motion vectors. In addition, the AMV creates a ranged search area that includes the nearest neighbor (NN) objects to the querier who issued a CR-based query. The effectiveness of the proposed AMV is demonstrated in simulated experiments.